Magneto-Structural Studies on Two Bis-μ-Methoxido-Bridged Dicopper(II) Complexes Supported by Subtly Different m-Xylyl-Based Terminal N3 Donor Binucleating Ligands - Singh, Ravindra; Lloret, Francesc; Nordlander, Ebbe; Mukherjee, Rabindranath (Zeitschrift fur Anorganische und Allgemeine Chemie, 2025)
Reactions of LXYL17 or LXYL18 (LXYL17 = α,α′-bis[((1-methyl-2-benzimidazolyl)methyl)-N-(6-methyl-2-pyridylmethyl)-amino]-m-xylene; LXYL18 = α,α′-bis[((1-methyl-2-benzimi-dazolyl)-methyl)-N-(2-pyridylethyl)-amino]-m-xylene) with [Cu(MeCN)4](ClO4) in CH2Cl2 at 298 K, subsequent exposure to dioxygen, and work-up from MeCN–MeOH, led to [CuII2(LXYL17)(μ-OMe)2](ClO4)2•0·5H2O (1) and [CuII2(L XYL18)(μ-OMe)2](ClO4)2•0.5MeCN (2). Structural characterization revealed their bis(methoxido)-bridged binuclear copper(II) structure. The well-known ring-hydroxylation of the xylyl-spacer has not been observed here. In both 1 and 2, each copper(II) center is terminally coordinated by a common N-methyl-benzimidazolyl nitrogen and a tertiary amine nitrogen; in 1, an additional terminal coordination is provided by a 6-methyl-2-pyridylmethyl nitrogen, generating a five-membered and in 2 it is by a 2-pyridylethyl nitrogen, generating a six-membered chelate ring. The binuclear copper(II) complexes have Cu…Cu separation of 3.0239(16) Å (1) and 3.0022(17) Å (2). The geometry around the two Cu(II) centers is almost ideal square-pyramidal in 1 (τ values: 0.05 and 0.015) and slightly distorted in 2 (τ values: 0.23 and 0.243). Magnetic susceptibility measurements (100–300 K) on 1 and 2 reveal strong antiferromagnetic coupling J = –916(10) cm–1 for 1 and J = –820(10) cm–1 for 2. The differential magnetic coupling is fine-tuned by structural differences exerted by two subtly different non-Schiff base m-xylyl-based terminal N3 ligands.
Keywords: crystal structures; di-μ-methoxido-bridged dicopper(II); m-xylyl-based binucleating ligands; magnetism